2014
DOI: 10.3389/fpls.2014.00407
|View full text |Cite
|
Sign up to set email alerts
|

Roles for jasmonate- and ethylene-induced transcription factors in the ability of Arabidopsis to respond differentially to damage caused by two insect herbivores

Abstract: Plant responses to insects and wounding involve substantial transcriptional reprogramming that integrates hormonal, metabolic, and physiological events. The ability to respond differentially to various stresses, including wounding, generally involves hormone signaling and trans-acting regulatory factors. Evidence of the importance of transcription factors (TFs) in responses to insects is also accumulating. However, the relationships among hormone signaling, TF activity, and ability to respond specifically to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 95 publications
(166 reference statements)
2
56
0
1
Order By: Relevance
“…Further studies showed that AtERF53 regulates drought and heat tolerances through interacting with RING domain ubiquitin E3 ligase for proteasome degradation4041. Arabidopsis octadecanoid-responsive AP2/EFR-domain transcription factor ORA47 (the orthologous of MeERF53) is strongly induced by salt stress, wounding and MeJA424344. Further studies suggested that ORA47 play a role in regulating a suite of genes related to biosynthesis and/or signaling transduction of phytohormone when plants are subjected to wounding and water stress45.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies showed that AtERF53 regulates drought and heat tolerances through interacting with RING domain ubiquitin E3 ligase for proteasome degradation4041. Arabidopsis octadecanoid-responsive AP2/EFR-domain transcription factor ORA47 (the orthologous of MeERF53) is strongly induced by salt stress, wounding and MeJA424344. Further studies suggested that ORA47 play a role in regulating a suite of genes related to biosynthesis and/or signaling transduction of phytohormone when plants are subjected to wounding and water stress45.…”
Section: Discussionmentioning
confidence: 99%
“…The amount and timing of ET production is then further regulated in an attacker-specific manner, which modulates the plant's defense response (Hu et al, 2011;Van der Ent and Pieterse, 2012;Groen and Whiteman, 2014;Rehrig et al, 2014). In addition to its role in defense, ET is also known to be an important regulator of developmental processes, and accordingly, ET-dependent defense patterns change during development.…”
Section: Attacker-induced Et Signalingmentioning
confidence: 99%
“…Plant defenses induced by caterpillars are mainly regulated by the phytohormone jasmonic acid (JA) and its derivatives such as methyl jasmonate (MeJA) and jasmonic acid-isoleucine (JA-Ile) (Thaler et al 2002; Turner et al 2002; Halitschke and Baldwin 2003; Koo and Howe 2009; Verhage et al 2011; Rehrig et al 2014). JA-Ile binds to the CORONATINE INSENSITIVE 1 (COI1) receptor thereby mediating the degradation of JAZ repressor proteins (Thines et al 2007).…”
Section: Introductionmentioning
confidence: 99%